DATABASE CAPABILITIES OF THE DJANGO FRAMEWORK (Web of Technology: Multidimensional Research Journal, 2024)
In this article, the statistics of the Python programming language's Django framework and its capabilities in working with databases are discussed. The article explains Django ORM and the methods for creating models. It provides an overview of the field types in models. The process of registering models and working with the admin panel settings is explained. Additionally, the possibilities of performing migrations and make migrations, as well as working with migration files, are outlined.